THE MODEL OF THE CONSTRICTION RESISTANCE OF A SLIDING ELECTRICAL CONTACT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This article is devoted to a theoretical study of the processes in a sliding electrical contact and the derivation of the formula for constriction resistance in the transient layer of electrical sliding contact taking into account the fractal heterogeneity of contact current-transmitting clusters, as well as the verification of the obtained theoretical formulas using a static experimental plant.